1993
DOI: 10.3758/bf03334140
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a gender difference in a haptic version of the water-level task

Abstract: The present experiment studied horizontality representation among men and women submitted to a haptic version of the water-level task. Without seeing the display, the subjects positioned a magnetic rod corresponding to the water line. It was found that the women performed as well as the men did, in contrast to the systematic male superiority under the standard visual version. Similarly, there was no gender effect when the subjects were instructed to set the rod horizontally in tilted containers. The absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…There are large individual differences in performance, and one occasionally finds a male advantage in the task (eg . However, gender differences are not invariably obtained in the water-level task (see Voyer et al 1995), and a male advantage is not found in haptic conditions (Berthiaume et al 1993;Heller et al 1999a;. Heller et al (1999aHeller et al ( , 1999b reported minimal gender differences in a haptic task that is very similar to the methodology used in the current study.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…There are large individual differences in performance, and one occasionally finds a male advantage in the task (eg . However, gender differences are not invariably obtained in the water-level task (see Voyer et al 1995), and a male advantage is not found in haptic conditions (Berthiaume et al 1993;Heller et al 1999a;. Heller et al (1999aHeller et al ( , 1999b reported minimal gender differences in a haptic task that is very similar to the methodology used in the current study.…”
Section: Introductionmentioning
confidence: 73%
“…Robert and her colleagues (Berthiaume et al 1993;Robert and Harel 1996;Robert and Ohlman 1994) reported a great deal of variability when examining the possibility of gender differences in the water-level problem. There are large individual differences in performance, and one occasionally finds a male advantage in the task (eg .…”
Section: Introductionmentioning
confidence: 99%
“…When spatial abilities are tested with nonvisual tasks, converging evidence indicates a lack of sex differences. Studies have shown that, using haptic instead of visual stimuli, the typical male superiority in the Water--Level test ( Berthiaume, Robert, St--Onge, & Pelletier, 1993) and in tests of field independence ( Walker, 1972) is eliminated. Similarly, women's greater overestimation of hill slants is eliminated under haptic conditions ( Proffitt et al, 1995).…”
mentioning
confidence: 99%
“…For most of these differences, there is an advantage in favor of males. However, there is evidence in support of a lack of sex differences in non--visual tasks [2], [17], [18], [19]. One interpretation of these data would suggest that men might have an advantage with visuo--spatial tasks, rather than with spatial tasks per se.…”
Section: Discussionmentioning
confidence: 62%